PREVALENCE AND ASSOCIATED FACTORS OF PERCEIVED STRESS AMONG ADOLESCENT GIRLS IN NAWABSHAH CITY, PAKISTAN - Parpio, Yasmin (Journal of Ayub Medical College Abbottabad, 2013)
Background: The aim of this study was to determine the prevalence and associated factors of perceived stress among female adolescent in Nawabshah City, Pakistan. Methods: This study was a sub-analysis of a parent research. Analytical cross-sectional design was used to achieve the study objectives. The study population comprised of school-going female adolescents aged 10-16 years resident of Nawabshah City. Perceived Stress Scale (PSS) and structured questionnaire were employed to measure the prevalence and associated factors of stress respectively. Multiple linear regressions were done to determine the predictors contributing to stress among female adolescents by using SPSS-17. Results: The mean (±SD) of perceived stress score of the respondents was 27.84±2.84 with median 28 and the values were ranging from 19-37 scores for female participants. The final model indicated that among adolescents whose fathers are unemployed, the estimated mean score of stress was 0.734±0.493 higher than adolescents whose fathers are employed. As the number of rooms in the house increased by one, the estimated mean stress score decreases by 0.213±0.082. Among adolescents whose parents quarrelled, the estimated mean score of stress was 0.158±0.051 higher than adolescents whom parents did not quarrel. Conclusion: Almost every second female adolescent (58%) reported stress symptoms. The father’s unemployment, number of rooms and parental quarrel is associated with risk of stress among female adolescents. Keywords: Stress, Adolescent, House-hold, Sindh, Pakistan, Family